Foreign ownership and the extensive margins of exports: Evidence for manufacturing enterprises in Germany - Horst Raff; Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2013)
We examine how foreign ownership of a firm affects the variety of goods that the firm exports and the number of countries it trades with. We construct a simple theoretical model of how foreign ownership may affect these extensive margins of exports and take this model to data from Germany, one of the leading actors on the world market for goods. In line with theoretical predictions we find that foreign-owned firms do export more goods to more countries after controlling for firm size, productivity and industry affiliation. These differences between foreign-owned firms and domestically controlled firms are highly statistically significant, and they are large from an economic point of view, with foreign-owned firms exporting up to 39% more goods to up to 31% more countries.
Keywords: F14; F23; 330; international trade; foreign ownership; multinational enterprise; foreign direct investment; extensive margins of exports; Germany